Host plants and population dynamics of the cob borer Mussidia nigrivenella Ragonot (Lepidoptera: Pyralidae) in Benin - Sétamou, M.; Schulthess, F.; Poehling, H.; Borgemeister, C. (Oxford University Press, 2000)
The ear borer Mussidia nigrivenella Ragonot is a polyphagous insect pest that feeds on various cultivated and wild plants. Surveys in four agro-ecological zones of Benin, conducted between 1993 and 1997, revealed ≈20 plant species from 11 plant families hosting the borer, but only 13 host plants enable the borer to develop to the pupal stage. Whereas, a maize crop usually supports one generation per season, several generations of M. nigrivenella were recorded on Parkia biglobosa (Jacq.) Benth. and Gardenia spp. Agro-ecological variation in the availability of wild host plants was noticed. The high abundance of wild hosts in the Guinea Savannas reflects the diversity of the natural flora in these zones. This abundance of M. nigrivenella host plants, coupled with their overlapping fruiting periods may be the main reason for the high pest densities on maize, although only one maize crop per year is grown in the Northern Guinea savanna. In a field experiment, the highest infestation levels and densities of M. nigrivenella occurred on Canavalia enseiformis (L.) DC. and Mucuna pruriens DC., two popular cover crops in West Africa. Maize and cotton were about equally suitable hosts. Thus, fruiting periods of C. enseiformis and M. pruriens should not precede that of maize, to avoid emerging M. nigrivenella populations shifting from the cover crops to maize.